Broken rituals: On the disintegrative power of conflictive media events on English Wikipedia. Issue 2 (1st June 2014) - Bilić, Paško
The article studies the integrative social capacities of media events, as hypothesized by Daniel Dayan and Elihu Katz, to understand the transformation of media events in the network era. Media events have become increasingly deterrritorialized and performed within cultures of spatial reach across different mediated centres that transcend national borders. In the global and network age media events are performed not only as integrative, but also as disruptive and conflictive. A case study follows closely the dynamic by which the audience of English Wikipedia editors reacts to global media reports, and reorganizes information to create new event spheres based on specific internal community norms and values. Due to a conflictive event, or a disaster marathon, it was difficult for the community to integrate the available information and it experienced a series of failed performances. The event was filled with anxiety, distrust and disagreements over its nature and outcome. Nonetheless, with the affordances of networked technologies and globally dispersed community of editors, Wikipedia performed the role of an online host community of the event by creating and renegotiating a new definition and meaning of the event.